Growth and Feed Efficiency of Chopped Grouper Fish Fry (Epinephelus fuscoggutatus> - Asih Amanda; Wiwin Kusuma Atmaja Putra; Tri Yulianto (Riau University, 2020)
This study aims to determine the best feeding rate (FR) in increasing feed efficiency and growth of Chopped grouper and to determine the efficiency and growth of Chopped grouper (Epinephelus fuscoguttatus x Epinephelus lanceolatus). This research was conducted in February-March 2020 for 42 days at the Household Scale Hatchery of the Marin Agri Sejahtera Cooperative, Tanjungpinang City, Riau Islands. The method used was experimental with a completely randomized design (CRD) with 4 treatments and 3 replications where K treatment (15% trash feed), A treatment (10% trash feed), B treatment (20% trash feed), treatment C (feeding 25% trash feed). The results of the study, through statistical analysis, showed that the papain enzyme dose was able to have a very significant effect.